Model For Economical Digital Smart Classes Indonesian Islamic Primary Schools (Madrasah Ibtidaiyah) In The 21st Century - Muhamad Arif; Mohd Kasturi Nor Abd Aziz; Yuldashev Azim Abdurakhmonovich (Universitas Nahdlatul Ulama Surabaya, 2023)
The emergence of the digital era is clear evidence of the evolution of the educational landscape. Ineducation, the creation of cost-effective digital classrooms may be the answer to future problems. In-expensive glass touchscreens are an alternative to digital classrooms. This research focuses on how tomake digital smart classes at MIN 3 Tangerang and Madrasah Ibtidaiyah Nurul Huda Cerme Gresik andhow to use digital smart courses in the learning process at MIN 3 Tangerang and Madrasah IbtidaiyahNurul Huda Cerme Gresik. This research will describe education in Madrasah Ibtidaiyah, Indonesia.Design/methodology/approach This research uses a qualitative case study methodology. This researchinvolved eight participants, including school administrators, digital space teachers, and the informationtechnology team. Use interview, observation, and documentation tactics to collect data. The data analysistechnique uses the methods of reduction, presentation, and interpretation of the important themes found.Limitations/Research Implications The results of the study revealed that there were two important elementsin this study, namely the learning process carried out in digital classrooms and the main obstacles to itsimplementation. Creating a digital smart class begins with the provision of infrastructure such as InFocus,a USB port, a USB cable, a dongle, a high-resolution camera, wireless, and a smart board (touch screen)connected wirelessly. Smart digital classes can really stimulate teacher creativity in producing the bestmedia for teaching materials. Obstacles to adopting digital courses include the limitations of gadgets thatsupport the implementation of digital classes, the competence of teaching teachers, and school regulationsin providing supporting facilities. Originality/Value This new research is expected to be the starting pointfor creating teaching materials that are simple, economical, and effective.